BRCA mutation: A review of breast cancer - Margret Chandira, R.; Prabakaran, M.; Jaykar, B.; Venkateswarlu, B.S.; Palanisamy, P. (Journal of Drug Delivery and Therapeutics, 2019)
In the present study, we focus on the causes of a major cancer type contributing to the major deaths due to cancer across the world. Breast cancer which accounts for more than approximately 29 to 34% affected to women posing a major cause of death due to cancer. In-situ carcinomas might arise in either ductal or lobular epithelium, but remain confined there, with no invasion of the underlying basement membrane that would constitute extension beyond epithelial boundaries. Approximately 29 to 34% of women with invasive breast cancer will die of their disease. This syndrome presents as skin changes resembling skin condition like redness, discoloration, or mild flaking of the nipple skin. As Paget’s disease of the breast advances, symptoms may include skin tingling, itching, increased sensitivity, burning and pain. There may also be discharge from the nipple. Approximately half of women diagnosed with Paget’s disease of the breast even have a lump within the breast. Keywords: Breast cancer, BRCA mutation, BRCA1, BRCA2.